Unaddressed regulatory issues in xenotransplantation: a hypothetical example - Kwisda, Koko (Frontiers in Transplantation, 2023)
The last years have seen a significant increase regarding technologies to manipulate genetic sequences and generate animals as source for xenoorgans. This has made the generation of genetically bespoke organisms a reality. This paper will analyze regulatory and practical aspects of such an innovative approach to xenotransplantation on the basis of a hypothetical case study applied to Germany and highlight gaps in the current regulation. This paper thus provides the basis for the legal debate within a specific country. Additionally, the identified gaps also pose a barrier towards harmonization of international regulation. This work therefore lays the groundwork for a guiding the international debate regarding the regulatory framework for solid organs xenotransplantation towards specific issues.